Empowerment for Children Aged Less Than 5 Years with Stunting: A Quasi-Experimental Design - Eli Amaliyah; Mulyati Mulyati (Jurnal Ners, 2020)
Introduction: Globally, more than one child in four under the age of five is too short for their age. Although attempts to reduce stunting have succeeded globally, stunting rates in Indonesia have unfortunately remained largely stagnant. However, few studies have been conducted in Indonesia, particularly in Banten to develop and evaluate the education program combining with nutrition rehabilitation intervention to reduce stunting. The purpose of this study was to test effectiveness of education and nutrition rehabilitation to increase community empowerment for stunting in Serang Banten.Methods: This study was conducted using a quasi-experimental design with the reversed-treatment non-equivalent control group design. The study used 200 people as research samples. The analysis tools used include descriptive statistics and paired t testsResults: The results of this study showed that education and nutrition rehabilitation effectively to increased community empowerment in overcoming children with stunting (p<0.05).Conclusion: Nutrition education and rehabilitation management needs to be improved in an effort to reproduce the status of malnutrition or malnutrition into normal nutritional status, particularly in Serang City.